Investigating English Teachers’ Perception About the Use of TPACK in EFL Learning - Sy, Yennie Ratnasari; Raja, Patuan; Sinaga, Tuntun (Universitas Islam Negeri Raden Intan Lampung, 2023)
Integrating technology in teaching and learning process has been a new phenomenon nowadays. Teachers need to use some kinds of technology in order to move from the conventional way to the new one and reach the learning objective more maximally. In fact, some teachers do not want to use technology in their teaching process because of their limited facilities and knowledge. One of supporting frameworks to this condition is the use of Technological Pedagogical Content Knowledge or known as TPACK. In relation with it, this paper is intended to investigate English teachers’ perception about the use of TPACK in their EFL learning. The subjects are 10 English teachers who teach in some of Senior High Schools in South Lampung Regency, Lampung Province. The data were gained using questionnaire and interview. Then, it was analyzed using descriptive qualitative method. The result then indicated that English teachers have good perception toward the use of TPACK in EFL learning.